Un système expert d'aide à la décision pour le développement durable de Djerba - Ghribi, Abdelhamid; Buchmann, Ernst; Khattali, Houcine (Municipalité de Djerba Houmt-Souk, 2007)
Keywords: Développement durable -- Djerba

Tafilelte Tajdite - Nouh, Ahmed (On Site Review Report, 2007)
Keywords: Urbanisme -- Mzab

Islam and the particularities of the Ibadi denomination - Hoffmann, Anne; Dittrich, Priska (Study Tour to Oman 2007, 2007)
A group of 29 forestry and agriculture students and faculty from the Universities of Kassel and Goettingen participated in a joint study tour to Oman from 24th of February to 10th of March 2007. The excursion´s aim was to gain first-hand impressions and knowledge on traditional and modern land- and resource use systems in Oman. Besides this thematic focus, we also tried to learn about the culture and way of living of the people in Oman. Therefore we are especially happy that we had the opportunity to exchange thoughts with Omani students from Sultan Qaboos University who joined part of our tour. This homepage is intended to present the topics that the study tour delt with as well as give some picture impressions from our two-week journey through Oman.
Keywords: Récits de voyage -- Oman

Rapport général sur la situation des droits humains des Imazighen de Libye (Tawalt, 2007)
Keywords: Vie politique -- Djebel Nefousa

Southern Tunisia's Encomium to Ben Ali - Godek, Robert F. (US Embassy, 2007)
Keywords: Judaïsme -- Djerba

Tunisian-American Chamber elects new board - Godek, Robert F. (US Embassy, 2007)
Keywords: Barouni, Mohamed Moncef